A Concern for Intraoperative Distractions and Interference: An Observational Study Identifying, Measuring, and Quantifying Both within the Operating Theatre. (11th December 2021) - Keogh, Shane; Laski, Deirdre
Abstract : Background . Modern surgical research has broadened to include an interest into the investigation of surgical workflow. Rigorous analysis of the surgical process has a particular focus on distractions. Operating theatres are inherently full of distractions, many not pertinent to the surgical process. Distractions have the potential to increase surgeon stress, operative time, and complications. Our study aims to objectively identify, classify, and quantify distractions during the surgical process. Methods . 46 general surgical procedures were observed within a tertiary Irish hospital between June 2019 and October 2019. An established observational tool was used to apply a structured observation to all operations. Additionally, a nine-point ordinal behaviourally anchor scoring scale was used to assign an interference level to each distraction. Results . The total operative observation time was 4605 minutes (mean = 100.11 minutes, std. deviation: 45.6 minutes). Overall, 855 intraoperative distractions were coded. On average, 18.58 distractions were coded per operation (std. deviation: 6.649; range: 5–34), with 11.14 distractions occurring per hour. Entering/exiting ( n  = 380, 42.88%) and case irrelevant communication ( n  = 251, 28.32%) occurred most frequently. Disruption rate was highest within the first ( n  = 275, 32%) and fourth operative quartiles ( n  = 342, 41%). Highest interference rates were observed from equipment issue and procedural interruptions. Anaesthetists initiated CIC more frequently (2.72 per operation), compared to nurses (1.57) and surgeons (1.17). Conclusion . Our results confirm that distractions are prevalent within the operating theatre. Distractions contribute to significant interferences of surgical workflow. Steps can be taken to reduce overall prevalence and interference level by drawing upon a systems-based perspective. However, due to the ubiquitous nature of distractions, surgeons may need to develop skills to help them resume interrupted primary tasks so as to negate the effects distraction has on surgical outcomes. Data for the above have been presented as conference abstract in 28th International Congress of the European Association for Endoscopic Surgery (EAES) Virtual Congress, 23–26 June 2020.